Selected aspects related to epidemiology, pathogenesis, immunity, and control of African swine fever - Woźniakowski Grzegorz; Frączyk Magdalena; Niemczuk Krzysztof; Pejsak Zygmunt (Journal of Veterinary Research, 2016)
African swine fever (ASF) is currently one of the most severe viral infections of domestic pigs, wild boars, and other hosts belonging to Suidae family. ASF is also considered as the most complex and devastating infectious and haemorrhagic disease of swine due to its severe socio-economic impact and transboundary character. ASF it is a notifiable disease and due to the lack of specific treatment and vaccine, the disease can be only limited by the administrative measures comprising wild boar hunting and stamping out of affected pigs. ASF occurred for the first time in Kenya in 1921 while in Europe (Portugal) the virus was detected at the end of the 1950s. In spite of successful eradication of this threat in a number of affected regions, the virus remains endemic in both feral and domestic pigs in Africa and Sardinia. The ‘new era’ of ASF started in 2007 after its re-introduction to Georgia. Following its intensive expansion, the virus spread to other Caucasian countries, including the territory of the Russian Federation. In 2014 the virus reached Ukraine, Belarus, and, consequently, European Union countries: Lithuania, Latvia, Estonia, and Poland. The occurrence of ASF in wild boars and pigs had a severe impact on both epidemiology and economy because of the national and international transport and trade consequences. Up to date, starting from the February 2014, eighty ASF cases in wild boar and three outbreaks in domestic pigs have been diagnosed. Taking into account the diverse rate of spread in Poland, this review aims to present and discuss the current state of knowledge on ASF including its epidemiology, pathology, transmission, and perspectives of control.